- #1

- 66

- 0

So far I have:

ln(x) + ln(x+1) = 1

ln(x)(x+1) = 1

e^1 = x(x+1)

e^1 = x^2 + x

This is where I get stuck.

Am I on the right track?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter r_swayze
- Start date

- #1

- 66

- 0

So far I have:

ln(x) + ln(x+1) = 1

ln(x)(x+1) = 1

e^1 = x(x+1)

e^1 = x^2 + x

This is where I get stuck.

Am I on the right track?

- #2

Homework Helper

- 6,223

- 31

e^1 = x^2 + x

Yes this is correct. Write e^1 as just e, which is constant.

If you move it to the other side you'll get:

x

Now how do you solve the equation ax

- #3

- 66

- 0

Yes this is correct. Write e^1 as just e, which is constant.

If you move it to the other side you'll get:

x^{2}+x-e =0

Now how do you solve the equation ax^{2}+bx+c=0?

I don't think x^2 + x - e = 0 can factor out, at least not without using the quadratic formula

- #4

Homework Helper

- 6,223

- 31

I don't think x^2 + x - e = 0 can factor out, at least not without using the quadratic formula

Then use the wquadratic equation formula and you'd solve for x.

Share:

- Replies
- 1

- Views
- 357

- Replies
- 7

- Views
- 472

- Replies
- 4

- Views
- 451

- Replies
- 12

- Views
- 425

- Replies
- 26

- Views
- 343

- Replies
- 3

- Views
- 431

- Replies
- 17

- Views
- 418

- Replies
- 10

- Views
- 701

- Replies
- 2

- Views
- 362

- Replies
- 4

- Views
- 645